Analisis Kemampuan Pemecahan Masalah Adaptasi Makhluk Hidup dengan Lingkungannya pada Siswa Kelas V Madrasah Ibtidaiyah - Hana Lestari; Nisa Fitiriani; Zulfikar Ismail (Intitut Agama Islam Nasional Laa Roiba Bogor, 2021)
One of the 21st century skills that students need to master is problem solving skills. The purpose of this study was to describe the problem solving abilities of fifth grade Madrasah Ibtidaiyah students in science subjects based on Polya rules. This research is a descriptive quantitative research involving 30 grade V students of Madrasah Ibtidaiyah Muhammadiyah 01 Ciasmara Pamijahan, Bogor Regency in the 2019/2020 academic year who were taken by purposive sampling. This research instrument is a test of problem-solving ability on environmental pollution material which contains 20 question items. The data processing technique was carried out descriptively by calculating the mean and percentage of each item to obtain a description of the student's problem-solving abilities based on Polya's rules. The results of this study indicate that (1) the average problem-solving ability of students in the aspect of understanding the problem is 82.43%, categorized as very good; (2) the average student's problem-solving ability in the aspect of making problem-solving plans was 53.84%, categorized as sufficient; (3) the average student's problem-solving ability in the aspect of implementing the problem-solving plan was 75%, categorized as good; (4) the average student's problem-solving ability at re-checking the solution was 39.42% in the poor category. So it can be concluded that the problem solving of class V Madrasah Ibtidaiyah students on environmental pollution material based on Polya's rules is in the good category with an average percentage of 65%. Keywords: